Municipality and food security promotion for disabled people: evidence from north-eastern Thailand. Issue 4 (18th May 2016) - Bualar, Theeraphong
ABSTRACT: This article puts forward a qualitative method for analysing the role of municipalities in promoting food security for people with disabilities, and examining barriers that affect their food access and food utilisation. Findings from face-to-face interviews with mayors, street vendors, and disabled persons from three major municipalities in north-eastern Thailand clearly indicate that a lack of knowledge of food security among mayors and street vendors, and financial restrictions suffered by families, have become insurmountable barriers to food among people with disabilities. The article recommends that municipalities should create paid employment for people with disabilities and incorporate universal design into infrastructure improvement.